GAINING SECURITY FEELING OF THE MAIN CHARACTERS REFLECTED IN JOHN STEINBECK'S NOVEL OF MICE AND MEN: A HUMANISTIC PSYCHOLOGICAL APPROACH - SETIAWAN, CANDRA (2007)
The object of the research is the novel entittled Of Mice and Men. The study gives focus on the way of main character gains security feeling.The major problem of this study is how Lennie Small as the one of major characters gains security feeling reflected in Of Mice and Men based on Humanistic Psychological approach. This research is aimed at analyzing the structural elements of Of Mice and Men and describing how Lenie Small gains the security feeling in the story based on Humanistic Psychological approach. This research paper is qualitative research. The object of the study is Of Mice and Men novel written by John Steinbeck. The primary data source is Of Mice and Men itself and the secondary data sources are the other sources related to the analysis such as books of literary theory and Humanistic Psychology. The method of data collection is documentation research. The technique of data analysis is descriptive analysis. The result of of the study reveals the way of Lennie Small gainas security feeling is unique, his disorder manner makes Lennie gains it mostly from his relative named George Milton. In Of Mice and Men, mostly Steinbeck describes how the rule of George Milton is very important toward Lennie's safety.